PENGEMBANGAN LKPD IPAS BERBASIS INQUIRY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Sholihah, Ana Putri; Hendra, Putra You; Pramudiyanti, Pramudiyanti; Dewi, Pramita Sylvia (LPPM UM Metro, 2024)
This research aims to develop LKPD Inquiry Learning-Based Science to Improve Critical Thinking Abilities of Elementary School Students which is valid and practical. The instruments in this research consisted of a validation questionnaire sheet and a student response questionnaire sheet. This research refers to the Borg & Gall development model up to the seventh stage which consists of: (1) research and data collection, (2) planning, (3) development of initial product drafts, (4) initial field trials, (5) revision of results trials, (6) main product field tests, (7) product revisions. The research results show that the development of inquiry learning-based worksheets with an average score from validators of 92.8% is in the valid category, the results of student response questionnaires in practicality trials at SDN 5 Jatimulyo with a percentage of 88% (very practical), the product effectiveness test results obtained an N-Gain test result of 0.72 which was categorized as high. Based on research results, the development of Inquiry Learning-Based Science Student Worksheets on Sound Material and Its Properties is suitable for use in the learning process in schools.